2017
DOI: 10.1186/s12906-017-1773-5
|View full text |Cite
|
Sign up to set email alerts
|

Membrane of Candida albicans as a target of berberine

Abstract: BackgroundWe investigated the mechanisms of anti-Candida action of isoquinoline alkaloid berberine, active constituent of medically important plants of Barberry species.MethodsThe effects on membrane, morphological transition, synthesis of ergosterol and the consequent changes in membrane permeability have been studied. Polarization and lipid peroxidation level of the membrane following berberine treatment have been addressed.ResultsMinimal inhibitory concentration (MIC) of berberine against C. albicans was 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…A large number of recent studies focused on the antifungal activities and the underlying mechanisms of action of BBR alone or in combination with other antifungal agents against Candida spp. (Dhamgaye et al, 2014 ; Da et al, 2016 ; Jing et al, 2016 ; Shi et al, 2017 ; Zorić et al, 2017 ). This study aimed to elucidate the mechanism underlying BBR tolerance in FLC-resistant C. albicans isolates and the effect of FLC on BBR tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of recent studies focused on the antifungal activities and the underlying mechanisms of action of BBR alone or in combination with other antifungal agents against Candida spp. (Dhamgaye et al, 2014 ; Da et al, 2016 ; Jing et al, 2016 ; Shi et al, 2017 ; Zorić et al, 2017 ). This study aimed to elucidate the mechanism underlying BBR tolerance in FLC-resistant C. albicans isolates and the effect of FLC on BBR tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…23,57,63,66,78,101 Berberine 161 peroxidation of membrane constituents. 237 Berberine also effectively protected mice infected with Salmonella typhimurium. 238 Further studies reported that this alkaloid could treat Helicobacter pylori-induced chronic gastritis by attenuating the BAFF-triggered Th17 response.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 96%
“…to Ar and Sc has not been reported before. The antifungal activity of Ar and Sc may be attributed to the inhibition of efflux pumps as it was shown for berberine, a natural isoquinoline alkaloid [18]. The measured lower effects of Sc is not known, however, the presence of efflux pump proteins belonging to ABC (ATP Binding Cassette) and MFS (Major Facilitators) superfamily might also be the responsible factors [18,19].…”
Section: Discussionmentioning
confidence: 93%